Alopecia Neoplastica due to Gastric Adenocarcinoma Metastasis to the Scalp, Presenting as Alopecia: A Case Report and Literature Review - Kim, Jung-Hee (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2014)
Alopecia neoplastica is defined as hair loss secondary to a visceral malignancy that has metastasized to the scalp. The scalp is a relatively common site of cutaneous metastasis, usually presenting as a single or multiple firm scalp nodules. Alopecia neoplastica is a well-recognized but rare presentation, and its pathogenesis is incompletely understood. Atrophy of the hair follicles due to tumor invasion of the scalp plays a role in the development of alopecia. Herein, we describe a 33-year-old woman with gastric adenocarcinoma who developed alopecia neoplastica while receiving cancer chemotherapy. Scalp biopsy revealed metastatic adenocarcinoma cells interspersed between collagen bundles and around hair follicles. Immunohistochemical analysis indicated that the tumor cells originated from the primary gastric adenocarcinoma. Therefore, she was diagnosed with alopecia neoplastica due to gastric adenocarcinoma. The findings from this report may be helpful for understanding the mechanism of alopecia neoplastica.